2018
DOI: 10.1055/s-0036-1591545
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic Aromatic Formylation with Difluoro(phenylsulfanyl) methane

Abstract: Difluoro(phenylsulfanyl)methane (PhSCF2H) was found to undergo a reaction with aromatic compounds mediated by SnCl4, through a thionium intermediate characterized by NMR and TD-DFT analyses, leading to the formation of a mixture of S,S′-diphenyl dithioacetal and aromatic aldehyde which, after oxidative hydrolysis, provides the aromatic aldehyde in good to excellent yields. The salient feature of the present work is the reaction of activated aromatic compounds containing a deactivating ester functional group, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Methyl 2-formylbenzoate (1a) and methyl 2-benzoylbenzoate (1h) were purchased from Tokyo Chemical Industry Corporation. Methyl 2-acetylbenzoate (1g) [17] was prepared from commercially available 2-acetylbenzoic acids (Tokyo Chemical Industry Corporation) by usual esterification using MeI, K 2 CO 3 /acetone at 25 °C for 12 h. Methoxy-substituted 2-formylbenzoates 1b [18], 1c [19], 1d [20], 1e [21], and 1f [22] were prepared according to the reported methods.…”
Section: Methodsmentioning
confidence: 99%
“…Methyl 2-formylbenzoate (1a) and methyl 2-benzoylbenzoate (1h) were purchased from Tokyo Chemical Industry Corporation. Methyl 2-acetylbenzoate (1g) [17] was prepared from commercially available 2-acetylbenzoic acids (Tokyo Chemical Industry Corporation) by usual esterification using MeI, K 2 CO 3 /acetone at 25 °C for 12 h. Methoxy-substituted 2-formylbenzoates 1b [18], 1c [19], 1d [20], 1e [21], and 1f [22] were prepared according to the reported methods.…”
Section: Methodsmentioning
confidence: 99%
“…The combined organic layers were washed with water (20 mL) and brine (20 mL), and then dried over anhydrous magnesium sulfate. After filtration and solvent removal, the crude residue was purified by column chromatography (30% EtOAc/hexane) to afford (1R,3S)-7-[(tert-butyldimethylsilyl)oxy]-5,10-dihydroxy-8,9-dimethoxy-1,3,6-trimethyl-1H-benzo[g]isochromen-4(3H)-one (22) To a 25 mL round-bottomed flask charged with 4,5,6-trimethoxy-7methyl-3-(phenylthio)isobenzofuran-1(3H)-one (7b) (0.3448 g, 1 mmol) and LiCl (0.04 g, 10% w/w) was added freshly distilled THF (4 mL). The stirred mixture was cooled to -60 °C followed by the addition of t-BuOLi in THF (1.1 mL, 1.0 M, 1.1 mmol).…”
Section: Paper Synthesismentioning
confidence: 99%
“…12 After considerable experimentation, it was found that upon treatment of 17 with PhSCF 2 H (1.5 equiv) and SnCl 4 (2 equiv) in CH 2 Cl 2 for 48 hours at room temperature, the required hindered phenylthiophthalide 7a was obtained directly from 17 in 60% yield. 22 A similar approach was employed for the synthesis of the hindered phenylthiophthalide 7b (Scheme 4 ). Starting from gallic acid, methylation with dimethyl sulfate gave methyl 3,4,5-trimethoxybenzoate ( 18 ), bromination of which with N -bromosuccinimide afforded 19 .…”
Section: Table 1 Structures Of the Naturally Occurring ...mentioning
confidence: 99%
“…However, it requires refluxing of the substrates in acidic conditions for long hours, which may be detrimental to the survival of other functionalities. , These methods require a tedious work-up procedure involving hydrolysis of intermediate imines and removal of TFA from the mixture after the completion of the reaction. , In recent times, the use of a metal catalyst (e.g., cuprous oxide) reduced the overall reaction time (Scheme ). Some milder methods have also been reported for formylation using a combination of active methylene derivative as the C1 source (e.g., dichloromethyl methyl ether) and toxic metal catalysts (such as TiCl 4 ). , Several of these reported synthetic protocols are often time-consuming, have a limited substrate scope, and are not suitable for bulk-scale synthesis due to cost and safety concerns, thereby limiting their potential commercial application in the industrial sector . Apart from these, several contemporary noble metal-catalyzed insertions of formyl groups into Ar-X or Ar–H , bonds with wide substrate scopes are also available.…”
Section: Introductionmentioning
confidence: 99%